Investigation of PACAP Fragments and Related Peptides in Chronic Retinal Hypoperfusion - Dora Werling; Dora Reglodi; Peter Kiss; Gabor Toth; Krisztina Szabadfi; Andrea Tamas; Zsolt Biro; Tamas Atlasz (Journal of Ophthalmology)
Pituitary adenylate cyclase activating polypeptide (PACAP) has neuroprotective effects in different neuronal and retinal injuries. Retinal ischemia can be effectively modelled by permanent bilateral common carotid artery occlusion (BCCAO), which causes chronic hypoperfusion-induced degeneration in the entire rat retina. The retinoprotective effect of PACAP 1-38 and VIP is well-established in ischemic retinopathy. However, little is known about the effects of related peptides and PACAP fragments in ischemic retinopathy. The aim of the present study was to investigate the potential retinoprotective effects of different PACAP fragments (PACAP 4-13, 4-22, 6-10, 6-15, 11-15, and 20-31) and related peptides (secretin, glucagon) in BCCAO-induced ischemic retinopathy. Wistar rats (3-4 months old) were used in the experiment. After performing BCCAO, the right eyes of the animals were treated with PACAP fragments or related peptides intravitreal (100 pM), while the left eyes were injected with saline serving as control eyes. Sham-operated (without BCCAO) rats received the same treatment. Routine histology was performed 2 weeks after the surgery; cells were counted and the thickness of retinal layers was compared. Our results revealed significant neuroprotection by PACAP 1-38 but did not reveal retinoprotective effect of the PACAP fragments or related peptides. These results suggest that PACAP 1-38 has the greatest efficacy in ischemic retinopathy.